Peripartum cardiomyopathy in a patient with hyperprolactinaemia. Issue 699 (January 1984) - Matharu, G. S.; Oelbaum, M. H.
Abstract : The clinical course of a patient with peripartum cardiomyopathy and hyperprolactinaemia is described. Hyperprolactinaemia may be a factor in this patient's heart failure.